Addressing Youth Issues in South Asia - Schuhmacher, Stella (World Bank, Washington, DC, 2017)
Youth are the cornerstone and the future of societies. It is of critical importance to adopt a life-cycle approach to child and youth development with a greater focus on the care, empowerment, and protection of girls and young women. This report focuses on youth, an age group defined as persons 15 to 24 years old. Five life transitions take place during this period, including: (1) learning after primary school age; (2) starting a productive working life; (3) adopting a healthful lifestyle; (4) forming a family; and (5) exercising citizenship. Youth in South Asia face many challenges during their transition into adulthood. They have to cope with high youth unemployment and youth illiteracy rates. The region is subject to both human-made emergencies and natural disasters, leading to the breakdown of health, education, and protection systems. Young men have been identified in conflict analyses across the region as key stakeholders in ongoing conflicts. This document contains an overview of concrete interventions from various sources, including around youth participation; changing norms, behaviors, and attitudes; gender sensitive development; preventing violent behavior; and child sensitive protection.